(untitled) (Annals of Medical Research, 2022)
Aim: Sugammadex is a recently developed γ-cyclodextrin agent that can reverse the effects of blockers such as rocuronium used to maintain non-depolarizing neuromuscular blockade. In this study, it was aimed to determine the effects of rocuronium and sugammadex applied to rats on the diaphragm. Materials and Methods: A total of 32, 8-10 week old Sprague-Dawley male rats were used in the study. Experimental animals were divided into 4 groups with 8 animals in each group. The control group did not receive any application with an experimental period. The sham group was given a volume of physiological saline equivalent to 16 mg/kg Sugammadex. Sugammadex group received 16 mg/kg sugammadex and sugammadex+rocuronium group received 16 mg/kg sugammadex followed by 1 mg/kg rocuronium. At the end of the experiment, diaphragms of all rats were removed. Tissues were evaluated histopathologically for the location of nuclei in the fibers, their serosal structures, cell infiltrations, fiber diameter and changes in morphology. Results: The cores of the fibers were located in the peripheral areas in sugammedex examinations. In this group, interstitial edema and an increased number of fibers were detected with some morphological changes compared to the Sham and Control Group. The diameters of the fibers were decreased compared to the Sham and Control Group. In the cross-sectional images of the rocuronium-sugammadex Group, it was found that the fiber diameter decreased compared to other groups, and edema increased in the interstitial area. This difference was found to be significant according to the statistical analysis using histopathological scoring (p<0.05).The increase in the fibers undergoing morphological changes was at a significant level. Conclusion: Sugammadex and Rocuronium-Sugammadex Complexes cause histopathological changes in diaphragmatic cells.